Tooth Loss-Associated Mechanisms That Negatively Affect Cognitive Function: A Systematic Review of Animal Experiments Based on Occlusal Support Loss and Cognitive Impairment - Wang, Xiaoyu; Hu, Jiangqi; Jiang, Qingsong (Frontiers in Neuroscience, 2022)
Background: There is a dose-response relationship between tooth loss and cognitive impairment, while tooth loss can be an independent risk factor for Alzheimer's disease. Tooth loss can also accelerate nerve damage and neurodegeneration. However, the associated mechanisms remain poorly understood. Objective: To conduct a systematic review of animal experiments on cognitive decline caused by the loss of occlusal support performed over the past 10 years and summarize the possible underlying mechanisms. Methods: “Tooth Loss”, “Edentulous “Tooth Extraction and Memory Loss”, “Cognition Impairment”, and “Dementia” were used as keywords to search PubMed, Embase, SCI, Science Direct, and OpenGrey. A total of 1,317 related articles from 2010 to 2021 were retrieved, 26 of which were included in the review after screening according to predetermined inclusion and exclusion criteria. Comprehensiveness was evaluated using ARRIVE guidelines and the risk of bias was assessed using SYCLE’S risk of bias tool. Results: The putative mechanisms underlying the cognitive impairment resulting from the loss of occlusal support are as follows: 1) The mechanical pathway, whereby tooth loss leads to masticatory motor system functional disorders. Masticatory organ activity and cerebral blood flow decrease. With reduced afferent stimulation of peripheral receptors, the growth of corresponding brain regions is delayed, the strength of the connections between neural pathways is decreased, and the corresponding brain regions degenerate. There is also a reduction in the retrograde transport of nutritional factors; 2) the aggravation pathway, in which tooth loss aggravates existing neurodegenerative changes, such as increased amyloid deposition in the brain. Tooth loss can also accelerate nerve damage through a reduction in nutrient intake; and 3) the inflammatory stress pathway, which involves chronic inflammation associated with tooth deficiency disorders. Tooth loss leads to chronic inflammatory stress in the central nervous system, changes in the levels of brain metabolism, activation of hypoxic stress-related pathways, and decreased expression of excitatory products in brain areas associated with cognition, leading finally to endoplasmic reticulum stress-induced apoptosis and mitochondrial autophagy. Conclusion: The loss of occlusal support may lead to cognitive dysfunction through the reduction of chewing-related stimuli, aggravation of nerve damage, and long-term inflammatory stress.